Drug Discovery for Leishmaniasis 2017
DOI: 10.1039/9781788010177-00199
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Compounds in Chemotherapy Against Leishmania

Abstract: Leishmaniasis today constitutes a major health problem and a mammoth task in the field of drug discovery. This is due to the limited arsenal of effective anti-leishmanial chemotherapeutics, painful parenteral administration, exorbitant price and numerous adverse side effects associated with current clinically established leishmanicidal drugs. These include meglumine antimoniate (Glucantime®), stibogluconate (Pentostam®), liposomal amphotericin B (AmBisome®) and miltefosine. Also, due to the frequent manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…A similar upfield shift is observed for both of the Sb compounds derived from R,S diols (2 and 3). In contrast, the compounds derived from the R,R/S,S diols exhibited either a smaller upfield shift (4) or a marked downfield shift (5). We observed a similar distinction between 2/3 and 4/5 in the 1 H NMR resonances of the OCH nuclei of the diols and bound diolates (Fig.…”
Section: Nmr Spectroscopysupporting
confidence: 57%
See 1 more Smart Citation
“…A similar upfield shift is observed for both of the Sb compounds derived from R,S diols (2 and 3). In contrast, the compounds derived from the R,R/S,S diols exhibited either a smaller upfield shift (4) or a marked downfield shift (5). We observed a similar distinction between 2/3 and 4/5 in the 1 H NMR resonances of the OCH nuclei of the diols and bound diolates (Fig.…”
Section: Nmr Spectroscopysupporting
confidence: 57%
“…Sb-containing therapeutics are still used, however, to treat the neglected tropical disease leishmaniasis. 5 Up to a million new cases of leishmaniasis are reported annually, mostly in low- and middle-income countries. 6 The Sb-containing antileishmanial drugs meglumine antimoniate (Glucantime) and sodium stibogluconate (Pentostam) are collectively known as the pentavalent antimonials.…”
Section: Introductionmentioning
confidence: 99%
“…The first-line treatment for leishmaniasis consists of the pentavalent antimonial drugs sodium stibogluconate (Pentostam, GlaxoSmithKline) (Figure ) and meglumine antimonate (Glucantime, Sanofi-Aventis) (Figure ). These pentavalent antimonials are administered intravenously for 28 consecutive days (20 mg of Sb/kg/day) and are variable in their efficacy against both VL and CL . In 1981, Croft showed that, for sodium stibogluconate, the active compound comes from the trivalent form of the drug .…”
Section: Leishmaniasismentioning
confidence: 99%
“…Thus, the synthesis and study of the properties of thiolated dioxiolene ligands and metal complexes based on them is relevant in view of the diversity of the properties manifested. Antimony(III/V) derivatives are used as antiparasitic agents in the treatment of leishmaniasis [53], and have potential as antitumor, cytotoxic, and antibacterial substances [54,55]. Along with biological activity, antimony complexes are promising compounds for the design of functional materials.…”
Section: Introductionmentioning
confidence: 99%